(untitled) (Federal University Gusau Faculty of Education Journal, 2025)
This study examined the effect of health education intervention on attitude towards Personal Protective Equipment (PPE) use among laboratory health workers in infectious disease hospitals in Kano State. To achieve this purpose, a pre-test, post-test, experimental and control group quasi-experimental design was used. The population of the study comprised sixty-nine (69) laboratory health workers in infectious disease hospitals in Kano State, Nigeria. A sample size of 60 respondents was drawn from the population using a multi-stage sampling procedure, which includes purposive, simple random, and availability sampling. The instrument for data collection was a researcher-structured closed-ended questionnaire, which was validated by five (5) experts in the Department of Human Kinetics and Health Education and the College of Medicine, Ahmadu Bello University, Zaria. The instrument was pilot-tested using Cronbach’s Alpha, and a reliability coefficient of 0.872 was obtained. Descriptive statistics of frequency and percentage were used to describe the demographic characteristics of the respondents. The research questions were answered using mean and standard deviation. Inferential statistics of paired sample t-test and independent sample t-test were used to test the stated hypotheses at a 0.05 level of significance. The result revealed that the health education intervention significantly improved attitudes (t = 17.91, p = 0.000) towards the use of PPE among laboratory health workers in infectious disease hospitals in Kano State. Additionally, there were significant differences between the experimental and control groups in attitudes (t = 15.71, p = 0.000) after the intervention. Based on the findings of the study, the study concluded that health education intervention significantly improved laboratory health workers’ attitudes towards the use of PPE in infectious disease hospitals in Kano State. Workers in the experimental group outperformed those in the control group in attitude towards the use of PPE after the intervention. The study recommended that the Hospital Management Board should organise periodic attitude-reorientation workshops and prioritise attitude-focused health education programmes on PPE use, especially in facilities with poor practices, to sustain positive behavioural change and align all staff with best PPE usage behaviours.